2005
DOI: 10.1038/nature03524
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cellular memory by reducing stochastic transitions

Abstract: cells fully induced with 0.5% galactose) of Gal3p and Gal80p, respectively (Supplementary Figs S2 and S4). Determination of galactose consumption rate To determine the galactose consumption rate, aliquots from cultures were filtered and the galactose concentration of the cell-free medium was analysed as follows. b-Galactose dehydrogenase was used to oxidize galactose in the presence of 2.5 mM NAD þ dissolved in a buffer containing 50 mM imidazole and 5 mM MgCl 2 pH 7.0 (ref. 30). Conversion of NAD þ into NADH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
562
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 478 publications
(598 citation statements)
references
References 29 publications
24
562
4
1
Order By: Relevance
“…4a). A similar study performed on GAL system of S. cerevisiae shows a bi-stable behavior for intermediate galactose concentrations (Acar et al 2005). It has been shown in this case that the positive feedback loop provided by Gal3p is responsible for the observed bistability.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…4a). A similar study performed on GAL system of S. cerevisiae shows a bi-stable behavior for intermediate galactose concentrations (Acar et al 2005). It has been shown in this case that the positive feedback loop provided by Gal3p is responsible for the observed bistability.…”
Section: Resultssupporting
confidence: 62%
“…Thus, the presence of the positive feedback brought about by Lac12p is critical for the observed wild-type response at various galactose concentrations. It has been experimentally observed that the GAL system of S. cerevisiae shows a bistable behavior when exposed to different preculturing conditions (Acar et al 2005). To verify if such a phenotype exists for the K. lactis KlGAL system, we simulated the dynamic model for two different preculturing conditions, that is, glycerol and galactose and subsequently grown on galactose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example is the galacatose ultilization network in yeast displaying bimodal patterns in the expression of the GAL family genes responsible for galactose metabolism [24]. A recent report about the presence of several global feedback loops overarching metabolic and transcriptional regulation in E. coli [25] indicates that in fact many more metabolically different stable phenotypes could be uncovered -if we were only able to experimentally probe metabolism of individual cells.…”
Section: Why Single Cell Metabolomics?mentioning
confidence: 99%